Active Targeting to Osteosarcoma Cells and Apoptotic Cell Death Induction by the Novel Lectin Eucheuma serra Agglutinin Isolated from a Marine Red Alga. (27th December 2012) - Hayashi, Keita; Walde, Peter; Miyazaki, Tatsuhiko; Sakayama, Kenshi; Nakamura, Atsushi; Kameda, Kenji; Masuda, Seizo; Umakoshi, Hiroshi; Kato, Keiichi
Abstract : Previously, we demonstrated that the novel lectin Eucheuma serra agglutinin from a marine red alga (ESA) induces apoptotic cell death in carcinoma. We now find that ESA induces apoptosis also in the case of sarcoma cells. First, propidium iodide assays with OST cells and LM8 cells showed a decrease in cell viability after addition of ESA. With 50 μ g/ml ESA, the viabilities after 24 hours decreased to 54.7 ± 11.4% in the case of OST cells and to 41.7 ± 12.3% for LM8 cells. Second, using fluorescently labeled ESA and flow cytometric and fluorescence microscopic measurements, it could be shown that ESA does not bind to cells that were treated with glycosidases, indicating importance of the carbohydrate chains on the surface of the cells for efficient ESA-cell interactions. Third, Span 80 vesicles with surface-bound ESA as active targeting ligand were shown to display sarcoma cell binding activity, leading to apoptosis and complete OST cell death after 48 hours at 2 μ g/ml ESA. The findings indicate that Span 80 vesicles with surface-bound ESA are a potentially useful drug delivery system not only for the treatment of carcinoma but also for the treatment of osteosarcoma.